Afscheid secr. P.B., B. van der Wiel (rechts) in Arnhem. Tijdens heropening jeugdherberg Arnhem en reünie medewerkers bij 40-jarig bestaan - Drent, Louis, (1973)
Afscheid secr. P.B., B. van der Wiel (rechts) in Arnhem. Tijdens heropening jeugdherberg Arnhem en reünie medewerkers bij 40-jarig bestaan.